A new endemic species of Alkanna (Lithospermeae: Boraginaceae) from hilly environments of west Iran - Zeraatkar, Amin; Khajoei Nasab, Farzaneh; Shirmardi, Hamzeh Ali (Phytotaxa, 2024)
Alkanna assadii Khajoei Nasab & Zeraatkar (Lithospermeae: Boraginaceae), a new species endemic to hills from Chaharmahal and Bakhtiari province of Iran, is described, illustrated, and compared with similar species. It is mainly compared with A. frigida, from which it is distinguished by its habit, height, basal leaves length and shape, cauline leaves size and shape, setae size, gland size, corolla color, and size, the status of the trichomes and glands in corolla, arrangement of the stamens in the corolla, pedicel length, calyx length, and bract shape and size. Notes on habitat, distribution, ecology, conservation status, and relationships are provided.